Effects of organic cultivation on soil fertility and soil environment quality in greenhouses - Tong, Lihong; Li, Jie; Zhu, Ling; Zhang, Shuo; Zhou, Hu; Lv, Yizhong; Zhu, Kun (Frontiers in Soil Science, 2022)
Organic cultivation has been considered as an important cultivation approach for sustainable agriculture in the world. Whether organic cultivation can mitigate the negative impact of agriculture on the environment especially in greenhouses is still unclear. The purpose of this study is to investigate the long-term impacts in soil fertility and environment quality through organic cultivation (OC), low-input cultivation (LC) and conventional cultivation (CC) in greenhouses after 15 years of cultivation. We found that the soil organic carbon (SOC) content in the OC treatment was 1.7 times of that in CC, 1.2 times of that in the LC treatments. The content of alkali nitrogen, available phosphorus and available potassium in the OC treatment was significantly higher than those in the LC and CC treatments. Probably due to the high input of organic fertilizers, increased content of heavy metals (Cu, Zn, Pb, Cd, Cr and As) were observed in the OC treatment. In addition, organic cultivation resulted in considerable residue accumulation of tetracycline antibiotics (TCs) and pesticides in the soil. Ecological risk assessment of soil pollutants showed that organic cultivation has the highest ecological risk index. The impact of organic cultivation on soil depends on the quantity and quality of the applied organic fertilizer, with the quality of organic fertilizer as the key factor restricting the development of organic cultivation.